Small Signal Stability Analysis of Two Stage PV Generation - Rizki Putra Prastio; Muhammad Aldo Setiawan; Rodik Wahyu Indrawan; Herlambang Setiadi (Journal of Advanced Technology and Multidiscipline, 2022)
Integration of photovoltaic (PV) based power plant have been increased significantly over the years. The integration of this devices is ranging on the small-scale capacity such as in distribution system and large-scale capacity such as in transmission system. Although, PV generation could provide sustainable and clean energy to the grid, they could also bring new challenge on the system stability. One of the stabilities of power system that can be affected by integration of this devices is small signal stability. Hence, it is important to capture the dynamic model of PV generation. This paper is on investigation of dynamic model of PV generation for small signal stability analysis. The simulation is carried out in MATLAB/SIMULINK environment. From the simulation results, it is found that by capturing the dynamic model of PV generation, the modes of the PV generation can be captured.